Characteristics of Wheat Noodle “Kitanokaori” Using Weakly Acidic Hard Water in Terms of Functional Qualities, Such as Inhibiting Postprandial Abrupt Increase in Blood Glucose - Sumiko Nakamura; Ken’ichi Ohtsubo (Foods)
Type 2 diabetes and osteoporosis are very serious diseases all over the world. We prepared noodles from ‘Kitanokaori’ (newly developed wheat) (KITs) using weakly acidic hard water, which showed a higher amount of resistant starch (9.0-fold) and calcium (2.7-fold) than noodles from Sanukinoyume (premium wheat) (SANs) using purified water. Furthermore, aged mice, which were fed a diet of KIT using weakly acidic hard water for eight weeks, showed lower postprandial blood glucose levels (BGLs) at 30 min after consumption than mice fed a control diet (SAN using purified water) (p < 0.05). Therefore, KIT seems promising in terms of health promotion through food. Additionally, the whiteness (WB) and brightness (L*) of wheat noodles using weakly acidic hard water showed higher values than ones using purified water. The texture of KIT using weakly acidic hard water showed few textural differences from noodles using purified water. The KIT using weakly acidic hard water would be acceptable in terms of palatability and bio-functionality in terms of delaying digestion.